Arginine Kinase: A Potential Pharmacological Target in Trypanosomiasis - A. Pereira, Claudio (Infectious Disorders - Drug Targets, 2014)
Trypanosomatids parasites have complex life cycles which involve a wide diversity of milieus with very different physicochemical properties. Arginine kinase is one of the key enzymes, responsible for the parasites’ metabolic plasticity, which maintains the cell energy homeostasis during environment changes. Arginine kinase catalyzes the reversible phosphorylation between phosphoarginine and ADP. The phosphagen phosphoarginine sustains high levels of cellular activity until metabolic events, such as glycolysis and oxidative phosphorylation, are switched on. In different unicellular and multicellular organisms including trypanosomatids, it was demonstrated that arginine kinase is an important component in resistance mechanisms to different stress factors, such as reactive oxygen species, trypanocidal drugs, pH and starvation. In addition, few arginine kinase inhibitors were identified during the lasts years, some of them with trypanocidal activity, such as polyphenolic compounds. All these unique features, in addition to the fact that arginine kinase is completely absent in mammals, make this pathway a favorable start point for rational drug design for the treatment of human trypanosomamiases.
Keywords: energy metabolism